The Use of Quizwhizzer Application to Improve Learning Outcomes to Reduce Potential Student Learning Loss - Ekaputra, Firdiawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The purpose of this study was to determine (1) the effect of quizwhizzer application on students' potential learning loss, (2) the effect of quizwhizzer application on students' learning outcomes. This research is a quasi-experimental research involving one pretest group and one posttest group. The subjects of this study were inorganic chemistry practicum students at the Jambi University Chemical Education Study Program, who were in class R-002 in the 2022/2023 academic year. This study used a pretest and posttest scheme. Student learning outcomes were measured through questions, and potential learning loss using a questionnaire. To test whether there is an impact of the quizwhizzer application on causing a decrease in potential learning loss or an increase in student learning outcomes, data on potential learning loss and subject learning outcomes were tested with a paired samples t test. The results obtained from this study are (1) quizwhizzer application has an influence on the possibility of students experiencing a decrease in learning loss and (2) quizwhizzer application has an influence on improving student learning outcomes.